Methodological considerations for icthyoarchaeology from the Tron Bon Lei sequence, Alor, Indonesia. (December 2017) - Samper Carro, Sofía C.; Louys, Julien; O'Connor, Sue
Abstract: The analysis of fish remains from Island Southeast Asian archaeological assemblages constitutes one of the main ways to examine human subsistence in the region. Methodological difficulties, however, such as the lack of diagnostic features permitting taxonomic and anatomical identification of fish bones, often results in only a small fraction of a fish assemblage analysed. Taphonomic processes are often not explicitly considered in many aquatic zooarchaeological analyses, leading to a dearth of information on how post-depositional processes may have affected the preservation of fish remains. Here we examine different methodological approaches to the analysis of fish elements recovered from an archaeological site in Indonesia, Tron Bon Lei (Alor, East Nusa Tenggara). We compare the results obtained through more traditional icthyoarchaeology methods, where only specific diagnostic bones are included in the analysis, to those attained when every bone recovered from the site is considered. In doing so, we also describe the entire archaeological sequence of Tron Bon Lei, which had previously only been partly presented. The analysis of the entire archaeological deposit confirms that the Alor inhabitants were intensively exploiting marine resources, while the contribution of terrestrial vertebrates to diet was very limited. Small individuals of inshore ray-finned fishes are more abundant in every layer, with limited evidence of fishing of larger individuals. Nevertheless, larger individuals and open water bony fishes are better represented in the late Pleistocene layers than in the late Holocene deposits. These results suggest changes in sea level may be the main factor responsible for these variations, although the role played by changes in fishing technology and human-induced resource depression needs to be considered. Our results show that analysis of the entirety of an assemblage allows for stronger inferences to be drawn about skeletal representation and taphonomic processes, and thus better informs human maritime subsistence strategies during the late Quaternary in Island Southeast Asia.